Mimikri Ikan di Bulan Suci - Zuhdan Aziz (IKOM UMY, 2015)
ln this dynamic life, odvertising has succeded to be come o brain wash machine ond a producer for consumerist society in many woys, tactics and strategies. Advertising as copitalism, which has metomorphosed with toctical mimicry (tike a chomeLeon), is alwoys readyto change its color, pattern, shape, ond also its face or anything else, odjust to the situation ond conditions. When societies celebrote and involve in religious processions like in the holy month (ramodhan), the ods will take o part dominantly, as the player, openly and stroight to the public. However, advertisements con camoufloge the content in to onother shope